PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KOTA BIMA - Ainun Wulandari; Kartin Aprianti (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effect of work motivation and organizational climate on performance. The approach used in this research is using an associative approach. The sample in this study was 40 respondents. The data collection techniques used were observation, questionnaires, and literature study. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that work motivation (X1) and organizational climate (X2) and simultaneously have a significant effect on consumer purchasing decisions at Hokky Mart Bima with an effect of 52%.